Correlation between sonochemistry and sonoluminescence at various frequencies - Zhou, Meifang; Yusof, Nor Saadah Mohd; Ashokkumar, Muthupandian (Royal Society of Chemistry, 2013)
The development of generic large-scale sonochemical reactors requires a fundamental understanding of how various experimental parameters affect the acoustic cavitation efficiency. With a view to expand the experimental database and knowledge, the changes to acoustic cavitation bubble structures, caused by covering the air-solution interface with a lid at various frequencies and power levels, have been investigated. The accompanying effects have been quantified using sonochemiluminescence and sonoluminescence as probes. It has been observed that the chemically active cavitation bubble population is dominant in the "open" (without lid) configuration and the sonoluminescing bubble population is dominant in the "closed" (with lid) configuration. A possible reason for such differences is the existence of a well-defined standing wave pattern in the closed system. © 2013 The Royal Society of Chemistry.